(untitled) (Analysis in Theory and Applications, 2017)
In this paper, by using the atomic decomposition of the weighted weak Hardy space WH_ω^1(R^n), the authors discuss a class of multilinear oscillatory singular integrals and obtain their boundedness from the weighted weak Hardy space WH_ω^1(R^n) to the weighted weak Lebesgue space WL_ω^1(R^n) for ωA_1(R^n).